Changes in the lesion surface suggesting transformation of oral potentially malignant disorders to malignancy - a report of eight cases - Moon-Jong Kim; Hong-Seop Kho (BMC, 2023)
Abstract Background In the case of oral potentially malignant disorders (OPMD), the possibility of malignant transformation of the lesion necessitates a decision on the need for an additional biopsy at each visit. Among many clinical characteristics, change on the lesion surface is one of the important factors that determine the need for additional biopsy at each visit. The purpose of the study was to provide information on the characteristics of lesions related to malignant transformation during the follow-up period of OPMD. Methods Eight patients (four men and four women) with OPMD that transformed into malignancy during long-term follow-up were included and their mean age was 65.8 ± 12.4 years. Clinical information and histopathological diagnosis were investigated at the initial visit and during the long-term follow-up period. The focus was on information on changes on the lesion surface at the time the lesion was confirmed to be malignant. The period from initial diagnosis to dysplasia and from dysplasia to malignancy was also investigated. Results The OPMD diagnoses were oral lichen planus or oral lichenoid lesions (n = 2), oral leukoplakia (n = 5), and hyperplastic candidiasis (n = 1). During the follow-up period of the lesions, when dysplasia was obtained by additional biopsy, changes in the lesions consisted of an increase in the size of the white or red area. The lesion surface of the OPMD showed verrucous, papillary, exophytic, corrugated, and ulcerative changes at the time of malignancy diagnosis. The period for the initial lesion to become dysplasia, from dysplasia to malignancy, and from the initial lesion to malignancy was very variable. Conclusions Attention should be paid to verrucous, papillary, exophytic, corrugated, and ulcerative changes on the lesion surface of OPMD. Considering that the period for OPMD to become malignant is highly variable, a longer follow-up of the lesion is necessary.